Aspectos clínicos, diagnósticos e desfechos de pacientes com neuroblastoma tratados em serviço de referência em oncologia pediátrica no sul do Brasil - Poletto, Pâmela Posser (2018)
Neuroblastoma is an embryonic tumor of the autonomic nervous system, typically developing in the adrenal gland or para-spinal ganglia. It occurs in children, with an average age of 17 months at diagnosis and is the most common cancer to be diagnosed in the first year of life. The clinical presentation is variable, having expansive mass characteristics in the region where it is housed. The objective of this study was to describe the diagnosis of Neuroblastoma in children treated at the Hematology-Oncology Service of the University Hospital of Santa Maria in the state of Rio Grande do Sul, Brazil, through the outcome and intercurrences experienced by them. The information was collected from the medical records of the patients treated between 01/01/1999 and 12/31/2015, and the data analyzed through averages and frequencies. After crossing the variables, the Pearson Correlation Coefficient was used and, finally, the Kaplan Meier survival curves were constructed. In this sample, composed of 28 patients, we found a frequency of 70.37% of high-risk neuroblastoma with Stage 4, with mean age at diagnosis of 29 months. The MYCN gene was tested in 82.15% of the patients, with 52.38% of them being amplified. Deaths occurred in 50% of our sample, and all patients belonged to Stage 4. Among the relapsed (n = 15), 20% were rescued. Overall survival was 89.3% in one year, 64.3% in two years, 53.6% in five years. Event-free survival at 1 year was 82.1% and in two years it was 53.6%. It is concluded that the results found are mostly consistent with the literature and that improvements are needed in the treatment regimens offered, especially for patients with high-risk disease and those with relapses.